MAPPING LEGAL-INSTITUTIONAL ARRANGEMENTS: A METHODOLOGICAL ROADMAP FOR STUDIES OF THE RELATIONS BETWEEN LAW AND POLITICS - Bucci, Maria Paula Dallari; Gaspardo, Murilo [UNESP] (Univ Federal Rio Janeiro Law Sch, 2024)
The proposed method of mapping legal-institutional arrangements aims to structure the interdisciplinary analysis of the relationship between political and legal elements in a given arrangement. Early versions of this methodological strategy have been applied, in the Law and Public Policy approach or in studies on democracy, within the disciplinary field of State Theory, of legal basis. The systematization of these applications aim at the interdisciplinary analysis of chosen arrangements, connecting sources of law and politics. They demonstrate good potential for deepening the legal perspective in dialogue with other areas, especially politics, while maintaining the analytical rationality of both areas. This article proposes to evolve in the consolidation of the method of mapping legal -institutional arrangements to create conditions for disseminating this type of analysis. The method can be applied in comparative studies, considering different configurations of the same arrangement over time or similar arrangements present in different sectors or in different geopolitical contexts. The methodology of the article is based on bibliographic reconstruction of the method contributions produced in the Law and Public Policy approach, in particular studies based on historical neo-institutionalism and those that resulted in the production of analytical frameworks, as well as the application of mapping in democracy studies. Finally, seeking to combine the contributions of the two lines, we present a methodological roadmap for mapping legal-institutional arrangements with their elements, stages, and application modes.
Keywords: Legal-institutional Arrangement; Mapping; Law and Public Policy; Democracy; Interdisciplinarity; State Theory